Increased Gustatory Response Score in Obesity and Association Levels with IL-6 and Leptin - Nesrine Remla; Zeyneb Hadjidj; Kamel Ghezzaz; Soraya Moulessehoul; Mourad Aribi (Journal of Nutrition and Metabolism)
Background. The aim of this study was to investigate the relationship between the circulating IL-6 and leptin levels with taste alteration in young obese patients. Methods. A retrospective case-control study was conducted in thirty obese patients and thirty age- and sex-matched healthy controls. Results. Circulating levels of IL-6 and leptin were significantly increased in obese patients than in controls. However, catalase and ORAC levels were significantly decreased in obese patients compared to controls. Additionally, obese participants had high scores for the detection of fats (gustatory response scores [GRS]; p<0.001). Moreover, IL-6 and leptin were strongly associated with GRS alteration among patients with GRS 4 (resp., OR =17.5 [95% CI, 1.56–193.32; p=0.007]; OR = 16 [95% CI, 1.69–151.11; p=0.006]). For the Mantel-Haenszel common odds ratio estimate (MH OR), IL-6 and leptin were strongly associated with obesity, in patients with either GRS 4 or GRS > 4 (resp., MH OR = 8.77 [95% CI, 2.06–37.44; p=0.003]; MH OR = 5.76 [95% CI, 1.64–20.24; p=0.006]). Conclusions. In a low grade inflammation linked to obesity, taste alteration is associated with high levels of IL-6 and leptin.